Islam beyond religion and politics: Islamisation in Southeast Asia. Issue 3 (2nd September 2018) - Arosoaie, Aida; Osman, Mohamed Nawab Mohamed
ABSTRACT: This special issue brings together six papers examining the emergence and development of Islamisation in the context of Southeast Asia. All papers problematise of the concept of Islamisation as merely an interplay between religion and politics. Instead, 'Islam' is understood as an episteme, a map-making exercise, which enables groups and individuals to render past, present and future experiences meaningful. The papers employ interdisciplinary frameworks, drawing on insights from law, political science, sociology and anthropology, to highlight how Islamisation entails both individual and group-led efforts to navigate complex configurations of modernity in the context of law, politics, media and education